2015
DOI: 10.1371/journal.ppat.1004647
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Evasion of Autophagy and Intracellular Killing by Human Myeloid Dendritic Cells Involves DC-SIGN-TLR2 Crosstalk

Abstract: Signaling via pattern recognition receptors (PRRs) expressed on professional antigen presenting cells, such as dendritic cells (DCs), is crucial to the fate of engulfed microbes. Among the many PRRs expressed by DCs are Toll-like receptors (TLRs) and C-type lectins such as DC-SIGN. DC-SIGN is targeted by several major human pathogens for immune-evasion, although its role in intracellular routing of pathogens to autophagosomes is poorly understood. Here we examined the role of DC-SIGN and TLRs in evasion of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(141 citation statements)
references
References 65 publications
2
137
0
2
Order By: Relevance
“…In P. gingivalis, it has been demonstrated that the accessory proteins FimC-E are essential for maintaining the structure and adhesive properties of FimA fimbriae (Nishiyama et al 2007). Binding of the C-type lectin DC-SIGN to Mfa1 fimbriae allows P. gingivalis to survive within dendritic cells (El-Awady et al 2015); the Mfa3-5 fimbrial tip complex is thought to be involved in this interaction. Therefore, our findings have implications for potential antibacterial therapeutic intervention for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In P. gingivalis, it has been demonstrated that the accessory proteins FimC-E are essential for maintaining the structure and adhesive properties of FimA fimbriae (Nishiyama et al 2007). Binding of the C-type lectin DC-SIGN to Mfa1 fimbriae allows P. gingivalis to survive within dendritic cells (El-Awady et al 2015); the Mfa3-5 fimbrial tip complex is thought to be involved in this interaction. Therefore, our findings have implications for potential antibacterial therapeutic intervention for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis avoids targeting to lysosomes in human DCs and instead traffics to vesicles resembling autophagosomes where it replicates. Indeed, selective engagement of DC-SIGN by P. gingivalis during uptake promotes evasion of lysosome fusion[70]. Induction of autophagy promotes the replication of A. phagocytophilum, C. burnetii , and P. gingivalis , while inhibition of autophagy blocks the replication of these pathogens in cell culture systems[63,67,7173].…”
Section: Xenophagy Beyond M Tuberculosis As Revealed By Cell Culturementioning
confidence: 99%
“…gingivalis in dendritic cells via a specific nonintegrin intercellular adhesion-grabbing molecule. 213 Porphyromonas gingivalis in association with macrophages induces toll-like receptor-2-mediated transactivation of CR3 through an inside-out pathway, and the activated CR3 interacts with P. gingivalis major fimbriae to downregulate interleukin-12, allowing P. gingivalis to enter and persist in macrophages. 189,212 Overall, P. gingivalis plays an essential role in subgingival microbial dysbiosis because of its participation in biofilm formation and modulation of host defenses, and the organism is recognized as a prototypic keystone pathogen of periodontitis.…”
Section: Virulence Determinants Functionmentioning
confidence: 99%